EVALUASI KEINDAHAN TAMAN LINGKUNGAN DI KOTA MALANG - Kurniawan, Hendra; Budiyono, Debora (BUANA SAINS, 2024)
Neighborhood Park is one of the many forms of Green Open Space in Malang City spread across five sub-districts which are generally managed by Department of Malang City Environment. Neighborhood Park is a park intended to serve residents within the scope of Neighborhood or Hamlet or urban village or sub-district which aims to serve community social activities. Neighborhood Parks in Malang City have the potential to contribute to the required Green Open Space area and provide city aesthetic. The purpose of this research is to evaluate the aesthetic value of Neighborhood Parks in Malang City. The research locations are Merjosari Park, Slamet Park, Merbabu Family Park, and Trunojoyo Park. The method used is Scenic Beauty Estimation (SBE). The results showed that Merjosari Neighborhood Park, Slamet Park, Merbabu Family Park, and Trunojoyo Park showed that the Neighborhood Park was in the category of high aesthetic, medium aesthetic, and low aesthetic. The Neighborhood Park that has high aesthetic is Merjosari Park, medium aesthetic are Slamet Park and Trunojoyo Park. Whereas low aesthetic is Merbabu Family Park